Urban green space and obesity in older adults: Evidence from Ireland. (April 2018) - Dempsey, Seraphim; Lyons, Seán; Nolan, Anne
Abstract: We examine the association between living in an urban area with more or less green space and the probability of being obese. This work involves the creation of a new dataset which combines geo-coded data at the individual level from the Irish Longitudinal Study on Ageing with green space data from the European Urban Atlas 2012. We find evidence suggestive of a u-shaped relationship between green space in urban areas and obesity; those living in areas with the lowest and highest shares of green space within a 1.6 km buffer zone have a higher probability of being classified as obese (BMI ⩾ 30 ). The unexpected result that persons in areas with both the lowest and highest shares of green space have a higher probability of being obese than those in areas with intermediate shares, suggests that other characteristics of urban areas may be mediating this relationship. Abstract : Highlights: We examine the association between living in an urban area with more or less green space and the probability of being obese as captured by objective measures of BMI. Geo-coded data on green space from the Urban Atlas 2012 are linked to the Irish Longitudinal Study on Ageing (TILDA). Data at individual level allows us to control for potentially confounding factors. We find suggestive evidence of a u-shaped relationship between green space in urban areas and obesity: those living in areas with the lowest and highest shares of green space have the highest probability of being obese.